Anthracnose Disease of Cashew (Anacardium occidentale Linn.)its Cause, Epidemiology and Control - Singh, Sujan; Sehgal, H. S.; Pandey, P. C.; Bakshi, B. K. (Indian Forester, 1976)
Cashew (Anacardium occidentale Linn.) is a valuable cash crop and a foreign exchange earner. Recently, there was an epidemic outbreak of an anthracnose disease of cashew in plantations in South India. The disease kills the flush, tender twigs and inflorelcence and thus seriously affects the yield of the fruit. The symptoms of the disease consist of dark brown shiny lesions followed by resin exuclation on the affected parts. Causal organism is identified as Collelotrichum gloeosporioides Penz. And is described as it occurs in nature. The control of the disease can be secured by chemicals using Bordeaux mixture or lime sulphur sprays. Spraying in the vulnerable period, quick coverage and spraying all diseased plantations, both private and government, are necessary to make any spray programme successful. The pathogen perennates on dead parts of the plant. Removal of infected parts of the plant and provision of wind breaks will also help in controlling the disease.